Analisis Simbolisme Jepang dalam Seragam Sekolah Menengah Pertama - Arum Sari, Puspa Ratu Suci; Hamidah, Idah; Puspitasari, Diana (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang; Vol 4 No 2 (2022)DO - 10.24843/JS.2022.v04.i02.p02, 2022)
The symbols on junior high school uniforms in Japan have different meanings. The purpose of this study is to describe the meaning of semiotics (denotative, connotative, and myth) in junior high school uniforms in Japan using Roland Barthes' semiotic theory. This research is a qualitative descriptive study research with literature study data collection techniques. The results of the analysis show six symbols whose meanings can be known, namely the school uniform was not only clothes worn by certain groups, but there are several semiotic meanings contained in parts of the school uniform. In addition, school coats are required to be in a dark color, which is a tradition in Japan where students are prohibited from wearing brightly colored coats. They wear a suit collar with a standard collar shape which is the best collar to use in any occasion, the symbol in the middle of the coat buttons means an identifier of the origin of the uniform, the coat pocket is decorative and is used to place an item. Then the purpose of using ties is for the student to be more confident and learn to dress neatly, white school shirts like school shirts in general symbolize cleanliness and innocence which makes students look formal when attending school, and school skirts that cover part or all of their legs part to show the feminist side of female students.